2008
DOI: 10.1093/hmg/ddn140
|View full text |Cite
|
Sign up to set email alerts
|

Usher syndromes due to MYO7A, PCDH15, USH2A or GPR98 mutations share retinal disease mechanism

Abstract: Usher syndrome (USH) is a genetically heterogeneous group of autosomal recessive deaf-blinding disorders. Pathophysiology leading to the blinding retinal degeneration in USH is uncertain. There is evidence for involvement of the photoreceptor cilium, photoreceptor synapse, the adjacent retinal pigment epithelium (RPE) cells, and the Crumbs protein complex, the latter implying developmental abnormalities in the retina. Testing hypotheses has been difficult in murine USH models because most do not show a retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 44 publications
(78 reference statements)
2
79
0
Order By: Relevance
“…In support, we show that the 3 proteins indeed interact. As with most Usher proteins, USH2A and GPR98 localize to the photoreceptor connecting cilium region, which plays a pivotal role in trafficking nascent proteins from inner to outer segment (15,16,23). Consistent with our genetic findings and protein interaction data, Pdzd7 is strongly localized in the basal part of the connecting cilium region in zebrafish and at the base of cilia in cultured RPE cells.…”
Section: Discussionsupporting
confidence: 85%
“…In support, we show that the 3 proteins indeed interact. As with most Usher proteins, USH2A and GPR98 localize to the photoreceptor connecting cilium region, which plays a pivotal role in trafficking nascent proteins from inner to outer segment (15,16,23). Consistent with our genetic findings and protein interaction data, Pdzd7 is strongly localized in the basal part of the connecting cilium region in zebrafish and at the base of cilia in cultured RPE cells.…”
Section: Discussionsupporting
confidence: 85%
“…In the absence of a reliable animal model, analysis of USH1B disease pathology is restricted to patients. Optical imaging and psychophysical testing of young USH1B patients revealed that photoreceptors are the first detectable site of disease ( Jacobson et al, 2008), highlighting the need to develop a gene replacement strategy that effectively targets both RPE and photoreceptors. Because the two allelic variants of human MYO7A are both relatively large, with coding sequences of 6534 and 6648 bp, respectively (Weil et al, 1996), treatment of USH1B will require a vector platform capable of delivering a relatively large cDNA.…”
mentioning
confidence: 99%
“…This suggestion is supported by a study of mice that contained mosaics of MYO7A-positive and MYO7A-null cells in their tissues. In these mice, the photoreceptor phenotype was demonstrated to be cell autonomous and not secondary to lack of MYO7A in the adjacent RPE (Jacobson et al 2008 ) .…”
Section: Myo7a -Mutant Micementioning
confidence: 94%